Optimizing the growth of caisim (Brassica juncea l.) using rabbit feces fertilizer as an eco-friendly organic alternative - Anugrah, Devi; Astriani, Dyah; Nurusman, Lutfah S (Universitas Ahmad Dahlan, 2025)
Caisim (Brassica juncea L.) is a widely consumed leafy vegetable that requires adequate nutrients for optimal growth. This study aimed to investigate the effect of rabbit manure on the growth of caisim plants, specifically focusing on fresh weight, dry weight, and root length. The experiment was conducted using a Completely Randomized Design (CRD) with five treatments and five replications. Treatments consisted of different soil-to-rabbit manure ratios: P0 (control, no manure), P1 (1:1), P2 (2:1), P3 (3:1), and P4 (4:1). The results showed that the application of rabbit manure significantly affected all three observed growth parameters. The best results were obtained in the P2 treatment (2:1 ratio), which yielded an average fresh weight of 21.902 g, a dry weight of 1.17 g, and a root length of 5.58 cm. These findings suggest that rabbit manure supplies essential nutrients, including nitrogen, phosphorus, and potassium, which contribute to enhanced root development and overall plant growth. The 2:1 ratio was found to offer the most effective nutrient balance for caisim cultivation. The implication of this study is that rabbit manure can serve as an environmentally friendly and effective organic fertilizer alternative to chemical fertilizers, supporting sustainable agricultural practices and offering a practical solution for enhancing the productivity of horticultural crops.